2015
DOI: 10.1097/jnn.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits in Breast Cancer Survivors After Chemotherapy and Hormonal Therapy

Abstract: Adjuvant treatments, specifically chemotherapy and hormonal therapy, have dramatically increased breast cancer survival, resulting in increased attention to the residual effects of treatment. Breast cancer survivors (BCS) frequently report that cognitive deficits are a particular source of distress, interfering with many aspects of quality of life. The literature on neuropsychological performance measures in BCS supports the reality of subtle cognitive deficits after both chemotherapy and hormonal therapy. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Therefore, reduced hormone levels may cause CRCI. Surprisingly, multiple studies have shown that impaired cognitive function areas such as speech memory, vocabulary fluency, and decision-making function appear after breast cancer patients undergo endocrine therapy [ 46 48 ], which may be related to the menopause period and timing of treatment [ 49 ]. Recently, Kathleen et al conducted a six-year prospective longitudinal study and found no endocrine therapy to adversely affect the cognitive function of breast cancer survivors.…”
Section: Pathogenesismentioning
confidence: 99%
“…Therefore, reduced hormone levels may cause CRCI. Surprisingly, multiple studies have shown that impaired cognitive function areas such as speech memory, vocabulary fluency, and decision-making function appear after breast cancer patients undergo endocrine therapy [ 46 48 ], which may be related to the menopause period and timing of treatment [ 49 ]. Recently, Kathleen et al conducted a six-year prospective longitudinal study and found no endocrine therapy to adversely affect the cognitive function of breast cancer survivors.…”
Section: Pathogenesismentioning
confidence: 99%
“…Yet, to my knowledge, whether post-menopausal cognitive decline is associated with a lower brain estrogen synthesis, due to lower circulating androgens and/or a failure of brain estrogen synthesis or action, is unknown and deserves further attention. In addition, aromatase inhibitors, which are a common treatment in breast cancer, have been associated with cognitive impairment (Frank et al 2015), psychiatric effects (Goodwin 2006; Rocha-Cadman et al 2012) or sexual dysfunction (Derzko et al 2007). As chemotherapy is provided systemically, aromatase blockade concerns all potential sources of estrogens.…”
Section: Summary and Emerging Questionsmentioning
confidence: 99%
“…While numerous quality of life (QOL) measures currently exist, they do not directly assess supportive care needs. Typically, needs are inferred from identified deficits in functioning, obtained by patients rating the presence and/or severity of an item but not whether it is a problem for which they need help [1, 25, 26]. In contrast, needs assessments directly identify and evaluate patients’ specific needs, as well as the perceived magnitude of those needs.…”
Section: Introductionmentioning
confidence: 99%